Acoustic radiation of circular plate including the attenuation effect and influence of surroundings - RDZANEK, W. (Archives of Acoustics, 1991)
This paper presents an analysis of the acoustic power of a thin circular plate, which includes internal dissipation in the plate's material and the influence of the acoustic wave radiated by the plate on it's vibrations. A fully fixed plate was accepted, which vibrates in a rigid and flat acoustic baffle under the influence of a definite external pressure, sinusoidal in terms of time, and radiates into a lossless and homogeneous liquid medium. The factor which forced vibrations was accepted as fixed. The acoustic power was calculated on the basis of the known distribution of vibration velocity into a series of eigenfunctions. The power radiated by the plate was expressed in the form of a strongly convergent series, so the frequency characteristics could be determined. Also the effect of the plate's internal attenuation was estimated, as well as the influence of the acoustic field radiated by the plate on the modification of its vibrations.